LSB METHODS OF COVERT MESSAGES TRANSMITION IN COMMUNICATION SYSTEMS (REVIEW) - Slobodianiuk Оlexander; Kostromytskyi, Andrii; Chebanenko, Viktor; Digtiar, Mikola; Onypchenko, Pavlo (Science-based technologies, 2024)
In the article are analyzed and classified methods of hiding messages in container data blocks and proposes a scheme for implementing the method of hiding information in an audio stream using the concept of the least significant bit method. Message hiding methods are aimed at ensuring the security of confidential information transmission by making it inaccessible to unauthorized access and detection. One such method is steganography, which uses multimedia data to hide secret messages. Images, text documents, and audio data are the most commonly used containers for steganographic hiding of information. The main advantage of steganography is its ability to complement encryption, making the data less obvious for detection. This makes it possible to hide the existence of the fact that secret information was transmitted, adding an additional layer of protection. Steganography uses multimedia data, such as images, text, or audio data, to embed secret messages. Using special algorithms, steganographic methods allow information to be embedded in media files in such a way that it cannot be detected without the appropriate keys or decoding methods. It complements encryption, increasing the security of information transmission by adding an additional layer of protection. Encryption converts data into an unreadable format that can be understood only by those who have the appropriate decryption key. Steganography, in turn, allows you to hide the very fact of the existence of encoded data, making it invisible to a potential attacker. This greatly complicates the task for those trying to intercept or interfere with the process of information transmission. The effectiveness of steganography is determined by such aspects as the capacity, security, and reliability of the hidden data. Capacity indicates the ability of the method to hold a sufficient amount of secret information without a noticeable increase in the size of the container. This is especially important because a significant increase in file size can raise suspicion and attract attention. Security refers to the ability to provide a high level of data invisibility so that the hidden information remains invisible to outside observers. Robustness refers to the resistance to changes or attacks on hidden information, including attempts to detect and remove hidden data. The application of steganography can be extremely broad and includes not only military or governmental activities, but also personal data protection, commercial and corporate security. Today, when the issues of data privacy and security are extremely acute, steganography is becoming increasingly relevant. In addition to traditional media such as images and audio, steganography can also be used in other areas such as network protocols and Internet communications. Hiding information in data packets or using steganographic methods in network protocols can provide an additional layer of security for the transmission of information on the Internet.